ISOLASI DAN KLONING GEN PENGKODE ENZIM MERKURI REDUKTASE (merA) PADA ISOLAT Streptomycetes - , Wahyu Aristyaning Putri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
merA is a gene that encodes mercuric reductase enzyme, an enzyme that plays a role in the reduction of Hg2+ into Hg0 that is less toxic. The gene is a part of operon system called the mer operon which contained on chromosomal and plasmid DNA. This study aims to isolate merA gene and clone this gene into cloning and expression vector. This research was carried out by testing the ability of resistance to mercury with Paper disk method. Linear plasmid and chromosomal DNA was isolated from Streptomycetes used alkaline lysis method. merA gene obtained then cloned into Blunt-TOPO and pMD20 vector. Transformation was done using competent cells of E. coli DH5Î±. The results showed that isolate AS1, AS2 and BR28 still have the ability to reduce mercury. They form clear zones less than 10 mm with the addition of 1 mM HgCl2 2 Î¼L. Because plasmid DNA isolation using the alkaline lysis method was not successful, then the isolation of chromosomal DNA using Spooling with a Glass Rod methods was done. Chomosomal DNA was used as a template to amplify the merA gene. In this study, the gene merA obtained on the size of 1456 bp. Cloning and transformation performed on E. coli DH5Î±. Br28âs merA gene was not isolated yet. Cloning of merA gene from AS1 and AS2 into pET-28c succesfully done with the correct of open reading frame. merA gene of AS2 succesfully expressed using pGEX-5x-1 vector. merA gene sequences of AS2 is closed to merA gene of Streptomyces lividans TK24 and AS1 closed to Streptomyces sp. CHR28 plasmid.